2016
DOI: 10.1111/sed.12298
|View full text |Cite
|
Sign up to set email alerts
|

Morphological expression of bedforms formed by supercritical sediment density flows on four fjord‐lake deltas of the south‐eastern Canadian Shield (Eastern Canada)

Abstract: High‐resolution swath bathymetry data collected in fjord‐lakes Pentecôte, Walker and Pasteur (eastern Québec, Canada) allowed imaging in great detail the deltas of four rivers in order to understand the factors controlling the formation and downslope evolution of bedforms present on their slopes. The morphometry and morphology of 199 bedforms reflect the behaviour of sediment density flows. The shape of the bedforms, mostly crescentic, and the relationships between their morphological properties indicate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 79 publications
(204 reference statements)
5
59
1
1
Order By: Relevance
“…A higher concentration of sediment waves is observed on the upper slope in coarse sediments. Previous studies have demonstrated that seasonal fluvial pulse discharges can generate gravity flows (Desloges and Gilbert, ; Van Rensbergen et al ., ; Gilbert and Butler, ; Gilbert et al ., ) and form sediment waves on delta frontal slopes (Wynn et al ., ; Girardclos et al ., ; Clarke et al, ; Hilbe and Anselmetti, ; Normandeau et al ., ; Symons et al ., ). The activity of gravity flows as a trigger mechanism for such sediment waves fits with the morphostratigraphy of the deltas in Grand Lake as stacked mass‐transport deposits are observed in the deltaic unit (U3a).…”
Section: Resultsmentioning
confidence: 99%
“…A higher concentration of sediment waves is observed on the upper slope in coarse sediments. Previous studies have demonstrated that seasonal fluvial pulse discharges can generate gravity flows (Desloges and Gilbert, ; Van Rensbergen et al ., ; Gilbert and Butler, ; Gilbert et al ., ) and form sediment waves on delta frontal slopes (Wynn et al ., ; Girardclos et al ., ; Clarke et al, ; Hilbe and Anselmetti, ; Normandeau et al ., ; Symons et al ., ). The activity of gravity flows as a trigger mechanism for such sediment waves fits with the morphostratigraphy of the deltas in Grand Lake as stacked mass‐transport deposits are observed in the deltaic unit (U3a).…”
Section: Resultsmentioning
confidence: 99%
“…Known turbidite thickness in East Lake (millimeter scale) and the runoff of the river which attains peaks of 1–2 m 3 /s during snowmelt (peak discharge) also suggest that the hyperpycnal flows are rather dilute. These low‐energy hyperpycnal flows are not erosive enough to produce large canyon‐channel systems that can concentrate flows downslope [e.g., Kremer et al ., , ; Normandeau et al ., ]. Instead, the flows being triggered at the delta front remain largely unconfined.…”
Section: Discussionmentioning
confidence: 99%
“…Developments in physical and numerical modelling of supercritical‐flow bedforms (Kennedy, ; Jorritsma, ; Foley, ; Winterwerp et al ., ; Parker & Izumi, ; Alexander et al ., ; Fagherazzi & Sun, ; Sun & Parker, ; Taki & Parker, ; Fildani et al ., ; Kostic & Parker, ; Alexander, ; Sequeiros et al ., ; Spinewine et al ., Kostic et al ., ; Paull et al ., ; Cartigny et al ., , ; Kostic, ; Balmforth & Vakil, ) have sparked a large number of observations of supercritical‐flow bedforms in modern systems (Fildani et al ., ; Lamb et al ., ; Duarte et al ., ; Jobe et al ., ; Babonneau et al ., ; Maier et al ., ; Covault et al ., ; Hughes Clarke et al ., ; Fricke et al ., ; Tubau et al ., ; Zhong et al ., ; Normandeau et al ., ; Symons et al ., ). Despite this common and well‐documented occurrence of supercritical‐flow bedforms, outcrop examples of deposits indicating these flow conditions in a fluvial setting (Fielding, ; Duller et al ., ; Fielding et al ., ; Ghienne et al ., ; Lang & Winsemann, ) or in a (deltaic‐) marine setting (Postma et al ., , ; Ventra et al ., ; Dietrich et al ., ) are sparse.…”
Section: Introductionmentioning
confidence: 99%